2015
DOI: 10.1161/circimaging.114.002262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coronary Artery Calcium Presence, Carotid Plaque Presence, and Carotid Intima-Media Thickness for Cardiovascular Disease Prediction in the Multi-Ethnic Study of Atherosclerosis

Abstract: Background Presence of coronary artery calcium (CAC), carotid plaque, and increased carotid intima media thickness (IMT) may indicate elevated cardiovascular disease (CVD) risk; however, no large studies have compared them directly. This study compares predictive utilities of CAC presence, carotid artery plaque presence, and high IMT for incident CVD events. Methods and Results Participants were from the Multi-Ethnic Study of Atherosclerosis. Predictive values of carotid plaque, IMT and CAC presence were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
188
4
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(219 citation statements)
references
References 24 publications
8
188
4
19
Order By: Relevance
“…7 Recent data using novel macrophage-specific imaging agents extend our knowledge of the basis of this disease and suggest significant macrophage infiltration in the vascular system. 10 ] These data expand a growing body of literature describing the unique nature of CVD and using advanced cardiovascular imaging to help us to extend our understanding of the disease. Similar to the study of Phan et al, 9 other studies using coronary computed tomography angiography have demonstrated an increased presence and extent of coronary artery disease, including noncalcified coronary plaque 11,12 and high-risk coronary plaque features, such as low attenuation and positive remodeling, accompanied by increased indices of immune activation.…”
Section: See Article By Phan Et Almentioning
confidence: 67%
“…7 Recent data using novel macrophage-specific imaging agents extend our knowledge of the basis of this disease and suggest significant macrophage infiltration in the vascular system. 10 ] These data expand a growing body of literature describing the unique nature of CVD and using advanced cardiovascular imaging to help us to extend our understanding of the disease. Similar to the study of Phan et al, 9 other studies using coronary computed tomography angiography have demonstrated an increased presence and extent of coronary artery disease, including noncalcified coronary plaque 11,12 and high-risk coronary plaque features, such as low attenuation and positive remodeling, accompanied by increased indices of immune activation.…”
Section: See Article By Phan Et Almentioning
confidence: 67%
“…Отдельные работы, имеющие целью оценку проявлений периферического атеросклероза, изучают прогрессирование по изменению лодыжечно-плече-вого индекса (ЛПИ). Большинство исследований включают пациентов либо исходно здоровых, либо имеющих определенную патологию (СД, ХБП), но без сердечно-сосудистых заболеваний (ССЗ) [1][2][3].…”
Section: The Risk Factors and Evaluation Criteria For Progression Of unclassified
“…Однако, в исследовании MESA [1], после исклю-чения из анализа пациентов с СД значение КИМ как в целом, так и выше 75 перцентиля не являлось пре-диктором сердечно-сосудистых событий. Наиболее значимым предиктором был коронарный кальций, оцененный при МСКТ (ОР 3,12, 95% ДИ 2,44-3,99, p<0,001).…”
Section: рисunclassified
See 1 more Smart Citation
“…These thoracic cavity confined comorbidities have been extensively characterized in the low-dose CT literature and integrating screening of heavily tobacco-exposed cohorts with best practice tobacco cessation approaches has been shown to enhance the cost utility of low-dose CT screening (16). In addition, clinical interventions have already been developed by the cardiology community as the implications of coronary calcium status are well established (17).…”
mentioning
confidence: 99%